Stakeholder perceptions and project performance - Davis, Kate; Machtynger, Liz; Di Maddaloni, Francesco (Cambridge University Press (CUP), 2025)
The chapter highlights the importance of stakeholders as a crucial aspect in understanding project behaviour. Effective stakeholder identification and management allows project managers to understand the needs and motivations of all individuals and groups who can impact or be impacted by a project. This information is crucial in ensuring project success by helping project managers to effectively manage stakeholder expectations and build strong relationships. The aim of this chapter is to enable the project manager to better consider and plan stakeholder management throughout the life of the project to maximise decision-making and benefits. It will elaborate on the challenges when including different stakeholder perceptions for project performance. The assumption is that it is essential to control the project’s outcome parameters through stakeholder expectations to minimise the chances of failure and maximise performance. Engaging stakeholders in any project environment, local regional, national or global all brings separate complexities. To deliver outcomes successfully, project managers need to develop a much clearer understanding of stakeholder perceptions, expectations and priorities to enable them to cope with any changes or uncertainty as the project evolves throughout the lifecycle.
Keywords: stakeholder expectations; stakeholder behaviour; stakeholder perceptions; decision-making; project performance; programme management; stakeholder management; project collaboration; project design